Open, multi-center randomized research and clinical program MINOTAUROS: intermediate data analysis - I. E. Chazova; V. B. Mychka (Кардиоваскулярная терапия и профилактика)
Aim. To assess indapamide (Arifon retard) effects on blood pressure (BP), carbohydrate, lipid, purine and electrolyte metabolism in patients with mild arterial hypertension (AH) and metabolic syndrome (MS). Material and methods. In total, 573 patients with mild AH and MS participated in MINOTAUROS Study (Patients with MetabolIc SyNdrOme - effecTiveness And ToleRability of ArifOn Retard in Arterial HypertenSion Treatment). All participants were randomized into two groups: 459 were administered Arifon retard and non-pharmaceutical treatment (Group I); 114 patients received only non-pharmaceutical treatment, without pharmaceutical antihypertensive therapy (control Group II). At baseline and after 12 weeks of therapy, BP, body mass (BM), waist circumference (WC), parameters of carbohydrate, lipid, purine, and electrolyte metabolism were measured.. Results. BM and WC decreased in both groups. Arifon retard therapy resulted in greater BP decrease, substantial improvement in carbohydrate and lipid metabolism, with unchanged purine and electrolyte metabolism parameters. Conclusion. Additional beneficial metabolic effects of Arifon retard, as well as its antihypertensive effectiveness, make it a diuretic of choice in treating MS and AH patients.